The role of coworker support in the relationship between moral efficacy and voice behavior: The case of hospitality students in Ecuador. Issue 3 (3rd July 2017) - Xu, Shi; Van Hoof, Hubert; Serrano, Ana Lucia; Fernandez, Lucia; Ullauri, Narcisa
ABSTRACT: This article explores the relationships among employee moral efficacy, coworker emotional support, coworker instrumental support, and employee voice behavior regarding abusive supervision in the hospitality industry in Ecuador: a high power distance culture. The results indicate that employees' moral efficacy predicted their voice behavior with regards to abusive supervision and that coworker emotional support strengthened this relation. However, an interaction effect between moral efficacy and coworker instrumental support on voice behavior was not found. This study provides a theoretical extension of the voice literature by introducing the roles of moral efficacy and coworker support, and has practical implications for the hospitality workplace.